Emotional intelligence and self-efficacy in L2 teaching: emotions of Spanish teachers in migration contexts - Masid Blanco, Ocarina; Planelles Almeida, Margarita (Círculo de Lingüística Aplicada a la Comunicación, 2025)
Language teaching is an emotionally charged activity (Richards, 2020), in which the emotions experienced are related to teachers’ perceived self-efficacy (Wyatt, 2018). These factors are strongly influenced by the teaching context (Tsang and Jiang, 2018; Wyatt, 2018). Specifically, the different actors involved in the care of migrants and refugees face feelings of work-related distress, burnout (Nonnis et al., 2021) and even secondary traumatic stress (Costa, 2018; Palanac, 2019). The teachers of these groups are often exposed to particularly stressful and distressing situations with a strong emotional impact (Costa, 2018). The aim of this study was to determine whether there are differences between teachers of Spanish as a foreign language in general contexts and teachers of Spanish for migrants and refugees in terms of the emotions they feel in relation to their teaching work, to explore the relationship between the emotions experienced, the level of perceived self-efficacy and emotional intelligence, and to find out whether the emotions experienced by teachers are affected by individual factors (age, academic training, years of teaching experience or students profile). For this purpose, a focused descriptive study was carried out with 144 Spanish teachers (73 teachers of Spanish as a foreign language in general contexts and 71 teachers of Spanish as a migrant language). The results show that, although teachers experience more positive than negative emotions and there is no difference in the level of perceived self-efficacy and emotional intelligence of Spanish teachers according to their work context, teachers of Spanish as a foreign language in general contexts experience more negative emotions than teachers of migrants and refugees. Furthermore, there is a relationship between the level of emotional intelligence, experienced emotions and perceived self-efficacy and that individual factors influence teachers’ emotions.